11-aza, 11-thia and 11-oxa sterol compounds and compositions - FRINCKE JAMES M (2013)
The invention provides compositions comprising formula 1 steroids, e.g., 16alpha-bromo-3beta-hydroxy-5alpha-androstan-17-one hemihydrate and one or more excipients, including compositions that comprise a liquid formulation comprising less than about 3% v/v water. The compositions are useful to make improved pharmaceutical formulations. The invention also provides methods of intermittent dosing of steroid compounds such as analogs of 16alpha-bromo-3beta-hydroxy-5alpha-androstan-17-one and compositions useful in such dosing regimens. The invention further provides compositions and methods to inhibit pathogen replication, ameliorate symptoms associated with immune dysregulation and to modulate immune responses in a subject using the compounds. The invention also provides methods to make and use these immunomodulatory compositions and formulations.